Existence and Exponential Decay of Solutions for a Wave Equation with Integral Nonlocal Boundary Conditions of Memory Type. (2nd September 2017) - Ngoc, Le Thi Phuong; Triet, Nguyen Anh; Ngoc Dinh, Alain Pham; Long, Nguyen Thanh
ABSTRACT: In this paper, we consider a wave equation with integral nonlocal boundary conditions of memory type. First, we establish two local existence theorems by using Faedo–Galerkin method and standard arguments of density. Next, we give a suﬃcient condition to guarantee the global existence and exponential decay of weak solutions. Finally, we present numerical results.